Biological control of microbial plant pathogens - Campbell, R. E. (Cambridge University Press, 1989)
The biological ways in which diseases of plants, caused by pathogenic microbes can be controlled without the use of chemical pesticides is the subject of this book. The basis of biocontrol (in microbiology, ecology, and plant pathology) is described and many examples of control measures in commercial use or development are given. There is increasing interest in biocontrol from the general public, environmentalists and the major world agrochemical companies, and this easily read text presents recent developments in the subject. The book provides the necessary references and literature citations to allow a more detailed investigation of particular diseases or control systems to be made. This is an important book that will be especially helpful to graduate and undergraduate students in botany, biology, microbiology, plant pathology, agriculture, horticulture, crop science and related courses